Gender differences favouring females in Estonian university students’ views of mathematics - Kaldo, Indrek; Hannula, Markku S. (NOMAD Nordic Studies in Mathematics Education, 2014)
This study reports on first-year Estonian university students’ views of mathematics. The data were collected from 970 university students of different disciplines. The participants completed a Likert-type questionnaire that was compiled from previously published instruments. The results reveal the importance of Mastery Goal Orientation as central to the structure of their views of mathematics. In this study, in five of six dimensions, females hold a more positive view of mathematics than do male students. Performance-Approach Goal Orientation was the only dimension in which we found no statistically significant gender difference. In all the other dimensions, the female respondents expressed a more positive affect towards mathematics: They showed a more powerful mastery orientation, valued mathematics more, felt more competent, perceived their teacher more positively, and cheated less frequently.